Vermicompost and humic substances in the production of strawberries cv. San Andreas in soils low in organic matter (Bioagro, 2026)
The growing demand for healthy fruits is driving the development of sustainable technologies to ensure food safety. In this context, the application of organic amendments represents a viable alternative for soils low in organic matter. It was evaluated the effect of three doses of vermicompost (0, 90, 180 g·planta-1) y humic substances (0, 50, y 100 g·planta-1) on yield, fruit quality, and soil properties of strawberry (cv. San Andreas) production. A randomized complete block design with a 3×3 factorial arrangement was used. The combination of 180 g·planta-1 of vermicompost y 50 g/plant of humic substances resulted in the highest yield (216.68 g·planta-1), with 90% of the fruits classified as extra quality.  Regarding soil quality, the organic matter content total nitrogen, y cation exchange capacity, increased. It has been demonstrated that the combined or individual application of organic inputs enhances the productivity y sustainability of strawberry cultivation in soils low in organic matter.
Keywords: Organic agriculture; organoleptic quality; yield